A New Reconstruction for Permian East Gondwana Based on Zircon Data From Ophiolite of the East Australian Great Serpentinite Belt. Issue 1 (10th January 2021) - Milan, L. A.; Belousova, E. A.; Glen, R. A.; Chapman, T.; Kalmbach, J.; Fu, B.; Ashley, P. M.
Abstract: The Great Serpentinite Belt of eastern Australia is a ∼1500 km long dismembered ophiolite assumed to be Cambrian based on studies of small (typically <50 m 2 ) exotic meta‐igneous inclusions despite contrasting ages (Cambrian—Devonian) and complex P‐T histories. To overcome these issues, we studied a ∼18 km 2 coherent block of dismembered ophiolite that provides robust geological context to sampling the ophiolite. Zircon U‐Pb‐Hf‐O isotope and trace analyses from three plagiogranite dykes cutting massive gabbro confirm ∼283–277 Ma ages and a mantle source. As a result, we argue older Cambrian to Devonian plagiogranite and subducted blocks were inherited from previous subduction events in eastern Australia. These findings allow us to match the Great Serpentinite Belt with the contemporary Dun Mountain ophiolite (New Zealand) and the Koh ophiolite (New Caledonia), thus supporting a new, integrated Pacific Gondwana margin paleogeography involving multiple arcs and subduction zones. Plain Language Summary: Ophiolites are fragments of oceanic crust and mantle that have been thrusted onto continents by tectonics. Ophiolites provide important records of oceanic lithosphere and for assessing the timing of significant tectonic events. Previous studies of the Great Serpentinite Belt of eastern Australia, established a ∼530 Myr age. However, studies focused on small (typically < 50 m 2 ) exotic fault bounded blocks of ophiolitic material of varying geological ages and complex metamorphic histories. By focusing on an intact 18 km 2 fragment of oceanic crust with reliable geological relationships and low degrees of metamorphism, our results show this ophiolite is far younger (∼280 Myr old). This age overlaps with ophiolites in New Caledonia and New Zealand on what was the paleo‐Pacific Gondwana margin. This new discovery leads to a new paleogeography for this period and improves geological links between eastern Australia, New Zealand, and New Caledonia. Key Points: A coherent 18 km 2 ophiolite block within the Great Serpentinite Belt, eastern Australia is Early Permian in age Cambrian to Ordovician ophiolite inclusions (often <50 m 2 ) do not date the main ophiolite but are inherited from previous subduction events A new reconstruction of the Early Permian east Gondwana paleogeography that incorporates coeval ophiolites in New Zealand and New Caledonia